Investigating the Importance of Creating a Personal Budget among Millenials, their Perception and Satisfaction: A Case Study of Eastern Mediterranean University - Windfried, Inom Missan Aldrich (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Many youths find it hard to manage their finances in an efficient way. When they build a monthly budget or financial plan or spending plan, and they try to reduce their expenditures, they will abruptly notice how they’re short of funds to take care of other main things. The state of our finances definitely has a direct influence and impact in making our lives more perplex; as a matter of fact most of our problems in life can somehow be related to, or can be gotten rid of by a proper handling of finances. This study sought to examine the perception and satisfaction the Eastern Mediterranean University (EMU) millenials have towards budgeting and inquired for ascertaining as to whether or not there is a need for better financial services advisory. According to the literature, millenials need to know how to create a written plan on how they intend to spend their money each month because their income is rare. A survey of 161 participants was used and the data was analyzed using a quantitative approach. Results showed EMU Millenials see the importance of building a budget and there is a need for better financial services.

ÖZ: Birçok genç, şahsi bütçe yapmanın ve verimli bir şekilde yürütmenin ne denli zor olduğunu bilmektedir. Her ay bir bütçe oluşturmaya ve masraflarını en aza indirmeye çalıştıklarında, birden önemli durumlar için para kalmadığını fark ederler. Bu durum, kişisel bütçe yapmayı daha da zor duruma sokar. Nitekim, hayatımızdaki finansal sorunların çoğunu doğru bir finansman kullanımı ile elimine edebiliriz. Bu çalışma, Doğu Akdeniz Üniversitesi Millenial neslinin (Y nesili = 1977-2000 yılı arasında doğanlar) bütçe yapma konusundaki algı ve memnuniyet derecesini incelemeye çalışmıştır. Literatüre göre, Millenial nesli gelirleri kıt olduğu için yazılı bir plan (bütçe) yapmak zorundadırlar. Bu çalışmada 161 kişiden oluşan bir örneklem kullanılmış ve veriler niceliksel bir yaklaşımla analiz edilmiştir. Sonuçlar DAÜ’deki milenial neslinin kişisel bir bütçe yapmasının ve bunu yaparken finansal hizmet alımının önemine işaret etmektedir.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Assoc. Prof. Dr. Bilge Oney.
Keywords: Banking and Finance; Personal Budgeting--Students--Eastern Mediterranean University--Famagusta (Cyprus, North); Budget; millenials; financial services advisory